Congenital Prepubic Sinus with Remnant Tissue Mimics Corpus Spongiosum: A Rare Case - Suleyman Celebi; Özgür Kuzdan; Serdar Sander; Nermin Gündüz; Seyithan Özaydın; Sevgi Yavuz (Georg Thieme Verlag KG, 2015)
Abstract A congenital prepubic sinus is a tract that originates in the skin and overlays the base of the penis; however, its embryologic basis is still debated. We herein present a case involving a 3-year-old boy who was admitted for examination of overlying tissue located a few centimeters distal to the dorsal base of the penis. Examination revealed a tiny sinus in the prepubic area, and 3 cm of tissue was attached to the sinus. Pathologic examination showed that the tissue was lined with squamous epithelium and continued along the sinus tract, which was lined with urothelial epithelium. According to Stephens' classification, the sinus appeared to be a variant of type 2 dorsal urethral duplication, and the remnant tissue mimicked the corpus spongiosum of the penis.